A fully self-powered, ultra-stable cholesteric smart window triggered by instantaneous mechanical stimuli. (July 2021) - Wang, Jiaqi; Meng, Cuiling; Wang, Chun-Ta; Liu, Chia-Hua; Chang, Yong-Hsiang; Li, Cheng-Chang; Tseng, Heng-Yi; Kwok, Hoi-Sing; Zi, Yunlong
Abstract: Smart windows (SWs), especially self-powered SWs, are desirable in a great variety of applications. Nowadays, nearly all SWs require continuous power supply enabled by batteries or energy harvesters such as solar cells, etc. However, batteries are usually with limited lifetime and potential environmental issues, while solar cells largely depend on the weather conditions. In this work, a fully self-powered, instantaneous-mechanical-stimuli-triggered, normally transparent smart window was developed based on an elaborately tailored cholesteric liquid crystal (LC) and a freestanding sliding triboelectric nanogenerator (FS-TENG). The transparency switching including transparency-to-haziness and haziness-to-transparency are facilely triggered by instantaneous TENG-charging and pressure-loading, respectively, with the high transparency contrast of 71.5% and the haze contrast of 61.8%. Both transparent and opaque modes can sustain for an extremely long time without continuous power supplies from energy harvesters. The smart window demonstrated in this work shows the capability of fully self-powered irradiation control for indoor temperature modulation and battery-free privacy information protection while the continuous power supply is no longer required, benefiting a wide variety of fields such as self-powered sunroofs, smart farming systems, motion-driven privacy protection systems, etc . Graphical Abstract: A fully self-powered, mechanical-pulse-triggered, normally transparent smart window was developed based on a cholesteric liquid crystal (LC) and a freestanding sliding triboelectric nanogenerator (FS-TENG). Both transparent and hazy states can last for a long time without continuous power supplies from environments, thanks to the bi-stable characteristic of the cholesteric LC material. The mechanical switching from hazy-to-transparent and transparent-to-hazy states are based on the TENG-charging and pressure-loading, respectively. ga1 Highlights: It is the first-time ever that an instantaneously-mechanically-triggered cholesteric smart window was developed. The transparency and opacity of the smart window can be switched back and forth by instantaneous mechanical triggering. After triggering, both transparent and opaque states can sustain for a long time without continuous charge feeding. This work correlates two important forms of energies in physics, mechanics and radiance, which is a totally new paradigm.